2021
DOI: 10.1111/pirs.12642
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization matter in the expenditure‐happiness nexus?

Abstract: This study aims to improve the regional well-being literature on the so-called "reversal issue" of the expenditurehappiness nexus, accounting for two main sources of heterogeneity: degree of urbanization and individual spending habits. Moreover, we investigate the role of happiness across the entire expenditure distribution using a quantile modelling approach. The results show that satisfaction has a positive, significant and non-linear effect on total expenditure across different urbanization categories. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Li [41] uses objective, subjective and social quality indicators for three Chinese cities, analysing the relationship between respondents' happiness and quality of life characteristics (objective and subjective) and social quality. Finally, several analyses have found that, among the three abovementioned sets of factors, the ones that most influence happiness are subjective indicators [31,42]. Thus, we propose the following hypothesis to determine whether happiness in European cities can be influenced by people's subjective assessment of their quality of life: Hypothesis 1 (H1).…”
Section: European Citizens' Happiness: Hypotheses Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Li [41] uses objective, subjective and social quality indicators for three Chinese cities, analysing the relationship between respondents' happiness and quality of life characteristics (objective and subjective) and social quality. Finally, several analyses have found that, among the three abovementioned sets of factors, the ones that most influence happiness are subjective indicators [31,42]. Thus, we propose the following hypothesis to determine whether happiness in European cities can be influenced by people's subjective assessment of their quality of life: Hypothesis 1 (H1).…”
Section: European Citizens' Happiness: Hypotheses Developmentmentioning
confidence: 97%
“…Therefore, the central concept of happiness is the subjective assessment of one's life or satisfaction with life [7,27]; they thus claim that happiness can be measured through "Satisfaction with life in this city". This way of measuring happiness is supported by the works of Diener [28], Diener and Inglehart [29], Veenhoven [30] and Bernini, Emili and Galli [31]. In addition, Moeinaddini et al [32] consider that happiness is synonymous with satisfaction of the experience, and this satisfaction can come from everything around you.…”
Section: Background On Happiness and The Mediating Effect Of Quality ...mentioning
confidence: 98%